2018
DOI: 10.3390/app8040645
|View full text |Cite
|
Sign up to set email alerts
|

A Review of MEMS Scale Piezoelectric Energy Harvester

Abstract: Piezoelectric energy harvester (PEH) is emerging as a novel device which can convert mechanical energy into electrical energy. It is mainly used to collect ambient vibration energy to power sensors, chips and some other small applications. This paper first introduces the working principle of PEH. Then, the paper elaborates the research progress of PEH from three aspects: piezoelectric materials, piezoelectric modes and energy harvester structures. Piezoelectric material is the core of the PEH. The piezoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 79 publications
1
35
0
Order By: Relevance
“…Finally, the deflections of both PEH devices at resonance can be approximated using Qa times the static deflections ( ) [27]: The bending moment function for each section of both PEH devices was determined through the Equation (20). The bending moment function for the first section, x (0,L s1 ), and for the second section, x (L s1 ,L s12 ), are given by Equations (21) and (22), respectively:…”
Section: Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the deflections of both PEH devices at resonance can be approximated using Qa times the static deflections ( ) [27]: The bending moment function for each section of both PEH devices was determined through the Equation (20). The bending moment function for the first section, x (0,L s1 ), and for the second section, x (L s1 ,L s12 ), are given by Equations (21) and (22), respectively:…”
Section: Of 16mentioning
confidence: 99%
“…The PEH devices have emerged in recent years due to the possibility of integration with MEMS [16][17][18]. For instance, several researchers have developed MEMS-based PEH devices for different applications [19][20][21][22]. Lu et al [23] reported a numerical modeling of a PEH cantilever for MEMS applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the interest in vibration has increased, owing to the rapid development of vibration energy harvesting technologies [16]. However, vibrations are also a potential problem for any application that includes moving components [17].…”
Section: Vibration Control and Dampingmentioning
confidence: 99%
“…Electrostatic and electromagnetic induction, and piezoelectricity can all typically be exploited as transducing mechanisms to convert mechanical energy into electrical [4]. However, from these, piezoelectric energy harvesters (PEHs) exhibit high-energy density and are, therefore, more suitable for practical applications [5]. Moreover, piezoelectric materials have an inherent capability to directly convert mechanical stress/strain energy into electrical energy, therefore, such devices are compact and possess simpler designs, compared to their electromagnetic and electrostatic counterparts.…”
Section: Introductionmentioning
confidence: 99%